2012
DOI: 10.1590/s0365-05962012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of squamous cell carcinomas among the population attended in the city of Tubarão, Brazil, between 1999 and 2009

Abstract: BACKGROUND: Skin cancer is the most common neoplasm in Brazil, with increasing incidence in recent decades. Data on the incidence of squamous cell carcinoma are scarce in southern Santa Catarina. OBJECTIVE: To establish epidemiological data on squamous cell carcinoma in Tubarão, State of Santa Catarina. METHODS: A cross-sectional review was conducted on anatomical pathology reports, positive for squamous cell carcinoma of the skin, found in the local laboratories. A convenience sampling method was used for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…In our study, the nodular subtype was seen at a rate in accordance with the literature, but mixed subtypes were ranked second. Corrêa and colleagues recorded that well differentiated types were the most frequently seen type of SCC, followed by the moderately differentiated type [30]. In our study, most of the SCCs were of the well differentiated type, and poorly differentiated (grade 3) and anaplastic or undifferentiated (grade 4) types were not observed.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, the nodular subtype was seen at a rate in accordance with the literature, but mixed subtypes were ranked second. Corrêa and colleagues recorded that well differentiated types were the most frequently seen type of SCC, followed by the moderately differentiated type [30]. In our study, most of the SCCs were of the well differentiated type, and poorly differentiated (grade 3) and anaplastic or undifferentiated (grade 4) types were not observed.…”
Section: Discussionsupporting
confidence: 50%
“…In Tubarão, Santa Catarina, a study of 1437 histopathological reports found an incidence rate of squamous cell carcinoma that reached 136.7 cases per 100,000 inhabitants in 2009. 15 …”
Section: Discussionmentioning
confidence: 99%
“…In the study carried out in Tubarão - SC, higher incidences were found of squamous cell carcinoma in ears and lips of men compared with women. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 4 , 6 The mechanism involves the production of thymine dimers in the TP53 gene, a tumor suppressor that contributes to DNA mutations and oncogenesis. 2 , 7 This association justifies the characterization of actinic keratosis as a precursor lesion and its higher prevalence among older adults. 1 , 6 , 7 …”
Section: Introductionmentioning
confidence: 80%